APLIKASI MOL DAUN KELOR DAN REBUNG BAMBU TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PAKCOY (Brassica rapa L.) - Arum Asriyanti Suhastyo; Bondan Hary Setiawan (Jurnal Ilmiah Media Agrosains, 2020)
Pakcoy plant cultivation can be carried out organically or inorganically, but to get high quality pakcoy plants, of course organic cultivation must be done immediately, considering the more residues generated from the use of inorganic fertilizers and inorganic pesticides One of the efforts made in cultivation without using materials -Chemicals that will damage the environment are the use of local microorganisms (Mol). Natural ingredients that contain growth stimulants and local microorganisms, including moringa leaves and bamboo shoots. This study aims to determine the effect of giving some moringa and bamboo shoots to the growth and yield of pakcoy plants. The research design used was factorial randomized block design, with two factors being tested, namely the administration of moles and the dose of fertilization. The first factor P1 = mol of moringa leaves, P2 = mol of bamboo shoots. The second factor is the fertilizer dose D1 = 60 ml / l, D2 = 70 ml / l, D3 = 80 ml / l. Each treatment was repeated 3 times to obtain 18 experimental plots. Data were analyzed using the F test, if significantly different, then continued with the Duncan Test (DMRT) level of 5%. The conclusion of this study showed that the application of moringa leaves and bamboo shoots on the growth and yield of pakcoy was not able to increase plant height, number of leaves and plant fresh weight. The mole dose of moringa leaves 70 ml / l is the optimum mole dose to give the highest average plant growth yield of 8,62 cm and the best yield of pakcoy weighing 3.45 g. and a dosage of Mol bamboo shoots 70 ml / l gave the best results for the growth of the number of leaves an average of 7,98 pieces. Kata kunci: rebung, dosis, kelor, organik Abstrak Budi daya tanaman pakcoy bisa dilakukan secara organik maupun anorganik, namun untuk mendapatkan hasil tanaman pakcoy yang bermutu tinggi tentunya budidaya secara organik harus segera dilakukan, mengingat semakin banyak residu yang dihasilkan dari penggunaan pupuk anorganik dan pestisida anorganik. Salah satu upaya yang dilakukan dalam budidaya tanpa menggunakan bahan-bahan kimia yang akan merusak lingkungan adalah dengan penggunaan mikroorganisme lokal (Mol). Bahan alami yang mengandung zat perangsang pertumbuhan serta mikroorganisme lokal, diantaranya adalah daun kelor dan rebung bambu. Penelitian ini bertujuan untuk mengetahui pengaruh pemberian beberapa konsentrasi Mol daun kelor dan rebung terhadap pertumbuhan dan hasil tanaman pakcoy. Rancangan penelitian yang digunakan adalah Rancangan Acak Kelompok faktorial, dengan dua faktor yang dicobakan yaitu pemberian Mol dan dosis pemupukan. Faktor pertama P1 = Mol daun kelor, P2 = Mol rebung Faktor kedua dosis pemupukan D1= 60 ml/l, D2= 70 ml/l, D3= 80 ml/l. Masing-masing perlakuan diulang 3 kali sehingga didapatkan 18 plot percobaan. Data dianalisis menggunakan Uji F, apabila berbeda nyata dilanjutkan dengan Uji Duncan (DMRT) taraf 5%. Kesimpulan penelitian ini menunjukkan Aplikasi Mol daun kelor dan rebung bambu terhadap pertumbuhan dan hasil tanaman pakcoy belum mampu meningkatkan tinggi tanaman, jumlah daun dan bobot segar tanaman. Dosis Mol daun kelor 70 ml/l merupakan dosis Mol yang optimum untuk memberikan hasil pertumbuhan rata-rata tanaman tertinggi 8,62 cm dan hasil pakcoy terbaik seberat 3,45 g. dan dosis Mol rebung bambu 70 ml/l memberikan hasil terbaik untuk pertumbuhan jumlah daun rata-rata sebanyak 7,98 helai.